When is the now in the here and there? Trans-diegetic music in Hal Ashby’s Coming Home - Aaron Hunter (Alphaville: Journal of Film and Screen Media, 2012)
While it would be a stretch to classify Hal Ashby as a postmodernist filmmaker (with that term’s many attendant ambiguities), his films of the 1970s regularly evince post-Classical stylistic and narrative strategies, including non-linear time structures, inter-textual self-references, open endings, and nuanced subversions of the fourth wall. Ashby’s most consistently playful approach to form comes by way of his integration and development of trans-diegetic musical sequences within his body of work. Music in Ashby films creates a lively sense of unpredictability, and each of his seven films of the 1970s employs this strategy at least once. Moreover, trans-diegetic music in Ashby’s films becomes a device that allows the director to elide moments in time. It functions as an editing tool, creating a bridge between often disparate events. However, it is also a narrative device that both compresses and stretches time, allowing for an on-screen confluence of events that at first appear to take place simultaneously or sequentially, but which actually occur over different moments or lengths of time. Yet while Ashby is not alone as a Hollywood director interested in exploring the formal possibilities that trans-diegesis might bring to his movies, film studies has begun only relatively recently to explore and analyse this technique. After briefly discussing the current critical discussion of trans-diegetic music and explicating patterns of its use in Ashby’s career, this paper explores an extended display of the strategy in the film Coming Home (1978). By interrogating its use as both narrative device and formal convention in this instance, the paper attempts both to understand trans-diegesis as a key component of Ashby’s filmmaking style and also to forge ahead in expanding the discussion of trans-diegesis within film studies.